Um estudo conciso da teoria dos semigrupos de operadores lineares - Sena, Harllen Araújo de (2022)
The present text comprehends to a brief study of the theory of semigroups of operators. We start exposing the preliminar theory, proceeding with the concept of semigroup proper, we developed its elementary properties and exposed some of the main results of the theory e.g. the E. Hille-K. Yosida-R. S. Phillips Theorem and G. Lummer-R. S. Phillips Theorem. We finish the work with the application of the theory to the study of some initial value problems.